Dendrite-specific remodeling of Drosophila sensory neurons requires matrix metalloproteases, ubiquitin-proteasome, and ecdysone signaling. - Kuo, C.T.; Jan, L.Y.; Jan, Y.N. (Proceedings of the National Academy of Sciences of the United States of America, 2005)
During neuronal maturation, dendrites develop from immature neurites into mature arbors. In response to changes in the environment, dendrites from certain mature neurons can undergo large-scale morphologic remodeling. Here, we show a group of Drosophila peripheral sensory neurons, the class IV dendritic arborization (C4da) neurons, that completely degrade and regrow their elaborate dendrites. Larval dendrites of C4da neurons are first severed from the soma and subsequently degraded during metamorphosis. This process is controlled by both intracellular and extracellular mechanisms: The ecdysone pathway and ubiquitin-proteasome system (UPS) are cell-intrinsic signals that initiate dendrite breakage, and extracellular matrix metalloproteases are required to degrade the severed dendrites. Surprisingly, C4da neurons retain their axonal projections during concurrent dendrite degradation, despite activated ecdysone and UPS pathways. These results demonstrate that, in response to environmental changes, certain neurons have cell-intrinsic abilities to completely lose their dendrites but keep their axons and subsequently regrow their dendritic arbors.